Test The Effectiveness Of Japanese Papaya Leaf Extract (Cnidoscolus aconitifolius) On Aedes aegypti Larvae Mortality : Uji Efektivitas Ekstrak Daun Pepaya Jepang (Cnidoscolus aconitifolius) Terhadap Mortalitas Larva Aedes aegypti - Ardiansyah, Syahrul; Nafsi, Faizatun; Hanum, Galuh Ratmana (Universitas Muhammadiyah Sidoarjo, 2023)
Dengue hemorrhagic fever (DHF) is caused by the dengue virus which is transmitted through the bite of the Aedes aegypti mosquito. Prevention of DHF can be done by using larvicides. Synthetic chemical larvicides are considered to have side effects in long-term use and can cause environmental pollution. So we need an alternative larvicides with natural ingredients from plants, namely Japanese Papaya plants. This study aims to determine the effectiveness of Japanese Papaya (Cnidoscolus aconitifolius) leaf extract on the mortality of Aedes aegypti larvae. This type of research uses an experimental study design. This study used 6 treatments with 4 repetitions consisting of control without treatment, P1 (0.2%), P2 (0.4%), P3 (0.6%), P4 (0.8%), and P5 (1%). Observations were made for 48 hours. From the research results obtained LC50 of 1.095%. The results of statistical tests using One-Way ANOVA showed that there was a significant effect on the mortality of mosquito larvae.